Varisonality and Surface Levels in Crystals with an Ionic Bond - Karimov, Z. I.; Oksengendler, B. L.; Suleymanov, S. Kh.; Doroshkevich, A. S.; Zatsepin, A. F.; Nikiforova, N. N.; Kulagina, N. A. (Research Highlights in Science and Technology Vol. 1, 2023)
Based on the rethinking of the Seitz scheme (1940), a new concept of the electronic structure of interfaces (including the surface) of ionically bonded crystals is proposed in the article. It is shown that the Coulomb long-range action transforms an ordinary structure with Tamm levels into a group of local levels from the Airy problem. In the same vein, the electronic structure of the interface of a layered structure with a fractal layer (in the form of a Sierpinski carpet) was studied. The obtained results turned out to be very useful for solving a number of problems in nanoelectronics.